PENGARUH PERUBAHAN MUKA AIR TANAH DAN TERASERING TERHADAP PERUBAHAN KESTABILAN LERENG - Wardana, I G. N. (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011)
Drenched rain soil is a cause in reduction of the soil strength in line with increasing ground saturation. Reduction of this strength reduces the slope stability which can cause sliding during the rainy season. Research was conducted by carrying out simulations on slopes using a Stable 2004 Program on different slope geometries, number of terraces and soil properties. The effects of drenched rain soil were simulated by changing ground water levels. The effects of slope geometries including inclination and height of slopes and earthquake loads were considered in the analyses. To ease the analyses, the terraces were grouped into 4 which were T1, T2, T3, and T4 having 1, 2, 3 and 4 terraces respectively. The slope without terrace is referred as T0, the slope inclination changed from 1:1 to 1:2 and 1:3 with different type of soils (clay, sand and variation of clay-sand). The analysis results showed that the increase in ground water level resulted in the reduction of slope stability for the slope of 1:1, 1:2, and 1:3, the safety factors increased with increasing number of terraces and the highest was thus in T4. For Sandy slope of 1:1 with T1 terrace, the increase in safety factor was noticeable, while for T2, T3, and T4 types they were almost the same. Sandy slopes of 1:2 and 1:3 with terraces changing from T1 to T4 causes the average safety factor increase in slightly. Clay slope with earthquake loads of 0.25 g and 0.45 g gave the average reduction in safety factor of 43% and 55% respectively. The earthquake loads of 0.25 g and 0.45 g caused reductions on safety factors of sandy slopes by 50% and 70% respectively.
Keywords: drenched rain slope, geometry, terrace, earthquake